PENENTUAN CELAH PITA ENERGI FILM TIPIS BARIUM STRONSIUM TITANAT (Ba1-xSrxTiO3) UNTUK x= 0,4 ; 0,5 DAN 0,6 - Dewi, Rahmi; Krisman, Krisman; Hidayat, Taufiq (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Barium Strontium Titanate (BST) thin film on the substrate glass was successfully fabricated by using sol-gel method. The purpose of this research is to obtain optical energy band gap value by adopting Tauc plot method with various composition and temperature. Obtaining of such information could be through identifying the degree of absorbance, degree of transmittance, the extent of refractive index, the usage of thin film and its quantified coefficients. Subsequently, the optical properties of thin film are characterized by using Ultraviolet-Visible Spectrophotometer with a thin film of Ba1-xSrxTiO3 subjected to temperatures of 650ÂºC. Upon subjected to temperature stated above, the wide energy band gap optical thin film Ba0,6Sr0,4TiO3 is in the range of 2.0 eV for Ba0,5Sr0,5TiO3 is in the range of 1.55 eV and for Ba0,4Sr0,6TiO3 is in the range of 2.0 eV. Keywords: Thin Film BST, Composition, Temperature, Energy Band Gap.